Improving the Training System of Qualified Specialists in the Field of Physical Education and Sports - Vaniyan, Sergei Barisovich; Behzoda, K. (International Journal on Integrated Education, 2023)
The article deals with the issues of regulating relations between the spheres of "science, education and production" in improving the system of training qualified specialists in the field of physical culture and sports, and creating a "cluster" system as an organization for monitoring the effectiveness of the work carried out, and also developed proposals and recommendations for further.